Post‐diagnosis weight loss as a prognostic factor in non‐small cell lung cancer. Issue 1 (4th December 2017) - Mytelka, Daniel S.; Li, Li; Benoit, Karin
Abstract: Background: Cachexia and its most visible manifestation, weight loss, represent important poor prognostic factors for patients with non‐small cell lung cancer. This work examines how severity of weight loss as an indicator of cachexia affects outcomes. Methods: In a retrospective observational study of electronic medical records, patients with non‐small cell lung cancer were monitored for weight loss from an initial assessment (within 2 months of index diagnosis) to a landmark at 5 months (at least 3 months after initial assessment). Patients who survived to the landmark were then followed to determine the association of baseline body mass index (BMI) and weight loss during the assessment period with outcomes. Patients were clustered to determine how BMI and weight loss related to survival as approximated by time of last appearance in the database, a strong proxy for time of death. Results: Twelve thousand one hundred and one patients were divided into 5 cachexia risk groups based on a combination of weight loss and initial BMI. More severe groups demonstrated progressively worse outcomes, with the most severe group surviving for a median of 263 days (95% CI 254–274) from index and having a 1‐year survival rate of 31%. The least severe group survived for a median of 825 days from index (95% CI 768–908) and had a 1‐year survival rate of 78%. Cachexia risk group was a stronger predictor of survival than any baseline variable, including disease stage, performance status, or age. Conclusions: In this study, we showed that increasing weight loss and, to a lesser extent, decreasing BMI, led to substantially worse outcomes for non‐small cell lung cancer patients independent of other variables. We suggest risk score groups that provide an improved approach for identifying poor prognosis patients with the greatest need.